Anxiety as readiness criterion of young athletes, specializing in middle distance running, for competitive activity - Kovalenko, A. N.; Khrisanfova, N. V. (The Russian Journal of Physical Education and Sport, 2017)
In sports activity the most general, integral index of an athlete`s readiness is sports result. Competitive activity success is mostly conditioned by the stability of an athlete`s performances. Nowadays in the sphere of training athletes, specializing in middle distance running, conditions, means and methods of physical and technical-tactical training are approximately equal. Hence, the main component of competitive activity becomes psychological training. Material. Theoretical analysis and experimental study of anxiety problem as one of the criteria, which influence readiness of young athletes, specializing in middle distance running, for competitive activity. Research methods: scientific literature analysis and summarizing, anxiety state estimation with the help of modified scale of personal competitive anxiety R. Martens (Y.L. Khanin), experiment, methods of mathematical statistics. Results. The effectiveness of psychological training at the stage of initial specialization is shown.There is some correlation between the level of anxiety and pre-start states of sportsmen in the experimental work. The offered methods of psychological training approbation among athletes showed positive result. During the use of the offered by us methodology two sportsmen improved their qualification from the 1st junior category to the 3rd adult category, 4 sportsmen changed their categories from the second junior to the 1st junior category. The trainer underlined considerable improvement of the results among 5 respondents, who didn`t manage to improve their sports category. Conclusion. During the research work the problems, concerning anxiety state study as the factor, which influences readiness of young athletes, specializing in middle distance running, for competitive activity were successfully solved.